2019
DOI: 10.3390/nano9060905
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Ga Doping on Crystal Structure and Polarimetric Pattern of SHG in ZnO Nanofilms

Abstract: The second-harmonic generation (SHG) in gallium doped ZnO (GZO) nanofilms was studied. The Ga doping in GZO nanofilms influenced the crystal structure of the films, which affected SHG characteristics of the nanofilms. In our experiments, a strong SHG response was obtained in GZO nanofilms, which was excited by 790 nm femtosecond laser. It was observed that the Ga doping concentrations affected, not only the intensity, but also the polarimetric pattern of SHG in GZO nanofilms. For 5.0% doped GZO films, the SHG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…This is probably because the Ga doping level is approaching to the saturation point in the ZnO thin film. The similar observation has been reported . Note also that no characteristic diffraction peaks of the Ga 2 O 3 crystal structure were observed [such as the (111) peak at 35.2°].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This is probably because the Ga doping level is approaching to the saturation point in the ZnO thin film. The similar observation has been reported . Note also that no characteristic diffraction peaks of the Ga 2 O 3 crystal structure were observed [such as the (111) peak at 35.2°].…”
Section: Resultssupporting
confidence: 88%
“…The similar observation has been reported. 38 Note also that no characteristic diffraction peaks of the Ga 2 O 3 crystal structure were observed [such as the (111) peak at 35.2°]. The d-spacing of the (002) lattice planes is determined using Bragg's law 2d sin θ = nλ, where d is the inter planar spacing, θ is the scattering angle, n is a positive integer, and λ is the angle of the incident wave (λ = 0.15,406 nm for Xray).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Another effective way to breaking centrosymmetry is by doping magnetic or rare earth ions and applying the electric field [74][75][76][77]. Zhang et al [78] showed that the impurity atom breaks the inversion symmetry of bilayer graphene, leading to the nonzero value of χ (2) .…”
Section: Magnetic Ordermentioning
confidence: 99%
“…Among various known materials, zinc oxide (ZnO) has a large exciton binding energy of 60 meV along with a direct wide band gap of 3.37 eV in ambient condition which qualifies its applications in many areas related to energy storage super capacitors [25], UV and gas sensors [26][27][28][29][30], optoelectronic devices [31,32], antireflection coatings [33], biosensors and photocatalyst [34,35] etc. Diversity of researches have been directed to study the ZnO nanoparticles in different shapes and goals such as photo luminescent ZnO nanoparticles for biological applications [36], ZnO nanoparticles modified carbon paste electrode for cyclic voltammetric study for drug analysis [37], for using in co-precipitation method in determining synthesis and characterization of Fe doped ZnO nanoparticles [38], influence of Ga doping on crystal structure and polarimetric pattern of SHG in ZnO nano films [39], in imaging of ZnO nanoparticles penetration in human skin in vitro and in vivo [40] to name a few. Several investigations were conducted to study the optical properties of ZnO based nanostructures such as ZnO-SiO 2 nanocomposites [41], zinc oxide doped aluminium films [42], ZnO nanoparticles [43], Mn-doped ZnO thin films [44], ZnO/polyvinyl alcohol (PVA) nanocomposite films [45], ZnO-Ag nanocomposites [46,47], ZnO/polymethyl methacrylate nanocomposite films [48], ZnO nanorods [49][50][51][52], Au/ZnO nanoparticale arrays [53], nanocomposite foils [54] and ZnO/polystyrene nanocomposite films [55].…”
Section: Introductionmentioning
confidence: 99%